Risk Factors for Low Back Pain in Weavers in Penggajawa Village, Nangapanda District, Ende Regency - Dewa, Patricia Putri Carenina Manuk; Roga, Andreas Umbu; Marni (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Lower back pain is a work-related disease that occurs and affects many people, including weavers. Back pain is often triggered by various hazard factors such as worker aspects, ergonomic risks, and psychosocial stress. Weavers who use Non-Machine Looms (ATBM) usually work in a sitting position with their legs straight on the loom without a backrest, with an unergonomic working posture for a long time. The purpose of this study was to analyze the risk factors for the occurrence of lower back pain in weavers in Penggajawa Village, Nangapanda District, Ende Regency. The type of observational analytical study with a cross-sectional approach, with a population of 100 weavers. The study was conducted in Penggajawa Village, Nangapanda District, Ende Regency in April-May 2025. The sampling technique used simple random sampling. The data analysis techniques used in this study were univariate andbivariate analysis. The results of the study showed that there was a relationship between age and the incidence of lower back pain in weavers, there was a relationship between Body Mass Index (BMI) and the incidence of lower back pain in weavers, there was a relationship between work duration and the incidence of lower back pain in weavers, there was a relationship between work posture and the incidence of lower back pain in weavers. Relaxation and muscle stretching are needed if you feel complaints while working, so that it can increase productivity while working.